(2‐Fluoro‐2, 2‐dinitroethyl)‐2, 2, 2‐trinitroethylnitramine: A Possible High‐Energy Dense Oxidizer. Issue 34 (9th October 2013) - Klapötke, Thomas M.; Krumm, Burkhard; Rest, Sebastian F.; Reynders, Martin; Scharf, Regina
Abstract: The fluorine‐containing polynitro energetic molecule (2‐fluoro‐2, 2‐dinitroethyl)‐2, 2, 2‐trinitroethylnitramine and the corresponding precursors were synthesized and investigated as potential high‐energy dense oxidizers. The compounds have been characterized by using various analytical methods, single‐crystal X‐ray diffraction, vibrational spectroscopy (IR and Raman), multinuclear NMR spectroscopy, elemental analysis, mass spectrometry, and differential scanning calorimetry (DSC) measurements. The suitability of the compounds as potential oxidizers in energetic formulations has been investigated. In addition, the heats of formation of the products were calculated with the program package Gaussian 09. Several detonation parameters such as the detonation pressure, velocity, energy, and temperature were computed using the EXPLO5 code. Furthermore, the sensitivity towards impact, friction, and electrical discharge was determined using the German Federal Institute for Materials Research and Testing (BAM) drophammer, a friction tester, as well as a small‐scale electrical discharge device. Abstract : We describe the synthesis and characterization of a new potential high‐energy dense oxidizer, (2‐fluoro‐2, 2‐dinitroethyl)‐2, 2, 2‐trinitroethylnitramine. Its potential in solid rocket propellants was investigated on the basis of quantum chemical calculations. Precursors to this material were characterized completely, and their energetic performances were estimated using the program package EXPLO5.